Murine model of autosomal dominant retinitis pigmentosa generated by targeted deletion at codon 307 of the rds-peripherin gene - FARRAR, JANE; HUMPHRIES, MARIAN; HUMPHRIES, PETER; LLOYD, DAVID G (Oxford University Press, 2002)
We introduced a targeted single base deletion at codon 307 of the rds-peripherin gene in mice, similar mutations being known to cause autosomal dominant retinitis pigmentosa (RP) in man. Histopathological and electroretinographic analysis indicate that the retinopathy in mice homozygous for the codon 307 mutation appears more rapid than that in the naturally occurring null mutant, the rds(-/-) mouse, suggesting that the rds-307 mutation displays a dominant negative phenotype in combination with that due to haplosufficiency. RP is the most prevalent cause of registered visual handicap in those of working age in developed countries, the 50 or so mutations so far identified within the RDS-peripherin gene accounting for up to 10% of dominant cases of the disease. Given the sequence homologies that exist between the murine rds-peripherin and the human RDS-peripherin gene, this disease model, the first to be generated for peripherin-based RP using gene targeting techniques, should in principle be of value in the work-up in mice of therapeutics capable of targeting transcripts derived from the human gene.
PUBLISHED
Keywords: Biochemistry